Penerapan Kegiatan Bercocok Tanam dalam Pembelajaran Berdiferensiasi pada Kemampuan Motorik Halus Anak Usia 5-6 Tahun - Nursih, Bestari; Rahmaningrum, Afifah; Nurifati, Nurifati; Fatimah, Siti; Farijah, Desi; Mashar, Riana (Magister Pendidikan Dasar FKIP Universitas Mataram, 2024)
The aim of this writing is to describe the application of farming activities in differentiated learning on the fine motor skills of children aged 5-6 years at the ABA AL-Furqon Kindergarten, Yogyakarta. This research uses a qualitative type through a descriptive approach. Descriptive research attempts to describe the results of observations and interpret the conditions that occur in relation to the topic taken. The research was conducted in December 2022 at the ABA AL-Furqon Kindergarten in Yogyakarta City. The selection of schools is based on purposive sampling, namely a technique for taking and determining samples based on certain considerations by the researcher. Data collection techniques use observation, interviews and documentation. The data obtained was analyzed using data analysis through the steps of data transcription, data reduction, data validation or triangulation, data presentation and drawing conclusions. The results show that farming is a process of interaction between children and the natural environment and there is cooperation between one child and another. So that the choice of farming method is appropriate for the development of fine motor skills in each child who has different characteristics or development. Because apart from being able to develop fine motor skills, there is increased social emotional development through cooperation and helping each other among children at the ABA AL-Furqon Yogyakarta Kindergarten.